CHRONOCLOCK - Mira Bashar Jamous; Tala Hamad (My University, 2024)
Workplace wellness and productivity are essential in modern living. ChronoClock is a Smart Propeller Clock designed to improve these areas by integrating advanced hardware and innovative features. ChronoClock uses a high-speed DC motor to spin 16 RGB LEDs in a propeller configuration, creating a unique and engaging time display. It includes a Real-Time Clock (RTC) module for precise timekeeping. The clock also has sensors to monitor CO2 levels, temperature, and humidity, providing real-time information about air quality. Motion sensors track inactivity and encourage regular breaks using the Pomodoro Technique to promote healthier focusing habits. A keypad and a mobile application allow users to customize the clock’s settings and appearance. ChronoClock enhances user interaction with its dynamic time display and real-time environmental monitoring. It helps maintain a healthy workspace by tracking air quality. The reminder and break features support continuous productivity and well-being. The keypad and mobile app enable users to easily personalize settings and features. ChronoClock is a significant improvement for modern living or workplaces,with advanced hardware with user-friendly design combined. This project shows how integrating wellness and productivity features into everyday tools can improve environments, making them healthier and more efficient.